Adult mortality from leukemia, brain cancer, amyotrophic lateral sclerosis and magnetic fields from power lines: a case-control study in Brazil Mortalidade por leucemia, câncer de cérebro e esclerose lateral amiotrófica em relação a campos magnéticos: estudo do tipo caso-controle no Brasil - Izabel Marcilio; Nelson Gouveia; Mário Leite Pereira Filho; Leeka Kheifets (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2011)
Recent publications renewed interest in assessing potential health risks for subjects living close to transmission lines. This study aimed at evaluating the association of both distance of home address to the nearest overhead transmission line and of the calculated magnetic fields from the power lines and mortality from leukemia, brain cancer, and amyotrophic lateral sclerosis. We carried out a death certificate based case-control study accessing adult mortality in the Metropolitan Region of São Paulo, in Brazil. Analysis included 1,857 cases of leukemia, 2,357 of brain cancer, 367 of amyotrophic lateral sclerosis, and 4,706 as controls. An increased risk for mortality from leukemia among adults living at closer distances to transmission lines compared to those living further then 400 m was found. Risk was higher for subjects that lived within 50 m from power lines (OR=1.47; 95% CI=0.99-2.18). Similarly, a small increase in leukemia mortality was observed among adults living in houses with higher calculated magnetic fields (OR=1.61; 95% CI=0.91-2.86 for those exposed to magnetic fields >0.3 µT). No increase was seen for brain tumours or amyotrophic lateral sclerosis. Our findings are suggestive of a higher risk for leukemia among subjects living closer to transmission lines, and for those living at homes with higher calculated magnetic fields, although the risk was limited to lower voltage lines. Os estudos avaliando riscos à saúde da exposição a campos magnéticos têm apresentado resultados controversos. Duas revisões recentes apontam a necessidade de mais investigações sobre o tema. O objetivo deste trabalho foi avaliar o risco de mortalidade por leucemia, câncer de cérebro e esclerose lateral amiotrófica em adultos em relação à exposição residencial a campos magnéticos gerados por linhas de transmissão. Foi realizado um estudo do tipo caso-controle de base populacional utilizando dados do sistema de informação de mortalidade na Região Metropolitana de São Paulo, entre 2001 e 2005. O risco foi avaliado em relação à distância das residências para as linhas de transmissão e para o campo magnético calculado em cada residência. Foram incluídos no estudo 1.857 casos de leucemia, 2.357 de câncer de cérebro e 367 de esclerose lateral amiotrófica, além de 4.706 controles. Encontrou-se um risco aumentado para leucemia em adultos morando mais perto das linhas de transmissão em comparação àqueles morando a mais do que 400 m. O maior risco foi entre os que moravam a até 50 m da linha (OR=1,47; IC95%=0,99-2,18). Também foi encontrado risco para pessoas morando em casas expostas ao maior campo magnético (OR=1,61; IC95%=0,91-2,86, para campos magnéticos >0,3 µT). Não foi encontrado aumento para tumores cerebrais ou esclerose lateral amiotrófica. Nenhum dos resultados foi estatisticamente significante. Os resultados sugerem aumento no risco de mortalidade por leucemia entre adultos expostos a campos magnéticos, mas os resultados devem ser interpretados com cautela, uma vez que todos os intervalos de 95% confiança englobavam o risco nulo.